A global bifurcation result for quasilinear elliptic equations in Orlicz-Sobolev spaces - Le, Vy Khoi (Topological Methods in Nonlinear Analysis, 2000)
The paper is concerned with a global bifurcation result for theequation $$ -\text{div} (A(| abla u|) abla u) = g(x,u,λ) $$ in a general domain $Ω$ with non necessarily radial solutions. Using a variational inequality formulation together with calculations ofthe Leray-Schauder degrees for mappings in Orlicz-Sobolevspaces, we show a global behavior (the Rabinowitz alternative) ofthe bifurcating branches.